Influence of endometrial thickness and pattern on pregnancy rates in in vitro fertilization‐embryo transfer - Shibahara, Hiroaki (Reprod Med Biol, 2002)
Aim : Our aim was to investigate the role of endometrial thickness and pattern in the pregnancy rate during an in vitro fertilization‐embryo transfer (IVF‐ET) cycle. Methods : Records of patients who underwent IVF‐ET at the Jichi Medical School Hospital during May 1995–December 1999 were evaluated retrospectively. Only cycles, in which endometrial thickness and pattern on the day of human chorionic gonadotrophin (HCG) administration were recorded, were analyzed in this study. Endometrial thickness was divided into three categories (A: < 10 mm, B: 10–14 mm, C: > 14 mm), and endometrial pattern was divided into two categories: triple line and non‐triple line. A total of 156 IVF‐ET cycles from 120 patients was evaluated. Results : There were no significant differences for both the endometrial thickness and pattern in the pregnancy rate during the IVF‐ET cycle (P > 0.05). Among the study groups, the triple‐line endometrial pattern was found to be 58.7% in group A, 84.0% in group B and 70% in group C. We found that in the triple‐line endometrial pattern, there was a significant difference between group A and group B (P < 0.01). Triple‐line endometrial pattern appeared significantly in younger women (33 ± 5.4 years) than in non‐triple‐line endometrial pattern (36 ± 5.2 years; P = 0.047). The minimum and maximum endometrial thickness where pregnancy occurred was 6.5 mm (two pregnancies) and 19 mm (one pregnancy), respectively. Conclusion : Endometrial thickness and pattern have no influence on the pregnancy rates in an IVF‐ET cycle, but patients with triple‐line endometrial pattern and group B endometrial thickness showed a better pregnancy outcome in the IVF‐ET treatment. (Reprod Med Biol 2002; 1: 17–21)